Formulation of fast-release gastroretentive solid dispersion of glibenclamide with gelucire 50/13 - Upadhyay P.; Pandit J.K. (My University, 2025)
Purpose: Fast-release gastroretentive solid dispersions of glibenclamide using gelucire were prepared to achieve improved bioavailability. Methods: Hot melt granulation technique was adopted to prepare solid dispersions (SDs) of glibenclamide in gelucire 50/13 and were compared with pure glibenclamide and physical mixtures of drug and gelucire using hot stage polarized microscopy, powder x-ray diffraction (PXRD), Fouriertransform infrared spectroscopy FTIR, bouyancy as well as by in vitro release and in vivo studies. Further aging studies were carried out for the samples. Results: PXRD showed that glibenclamide was present in SD in an amorphous form while FTIR spectroscopy revealed the presence of hydrogen bonding in the SDs. In vitro buoyancy was found for 11 h and there was improvement in solubility and dissolution rate for all test formulations. Formulations were found to follow Zero order kinetic. During aging study, no decrease of in vitro drug dissolution was observed over 3-month period. Crystallinity in the SDs was observed following aging. A more pronounced lowering of blood glucose level in Wistar rats compared with the pure drug, suggests that the test formulations are superior. Conclusion: This study demonstrates the high potential of hot melt technique for obtaining stable fastrelease gastroretentive solid dispersions of poorly water soluble drug using polyglycolized glycerides as carriers © Pharmacotherapy Group, Faculty of Pharmacy, University of Benin, Benin City, 300001 Nigeria.